The influence of KCl concentration on the gelation of myofibrillar protein giant squid (Dosidicus gigas) due to molecular conformation change - Niu, Fuge; Ma, Shuang; Zhang, Xiuzhen; Ritzoulis, Christos; Chen, Yueyue; Pan, Weichun (Frontiers in Nutrition, 2023)
Introduction Protein gelation process is of importance in food industry. The objective of this study is to investigate the influence of salt concentration variation, which induced protein conformation change, on protein’s intermolecular interactions and its gelation process. Methods Paramyosin has been separated and purified from myofibrillar protein extracted from giant squid. Then Giant squid’s paramyosin molecular mass and intermolecular interactions were quantified by means of light scattering techniques. Finally, the micro-rheology study via diffusing wave spectroscopy (DWS) technique revealed that this conformation change dramatically affected myofibrillar protein gelation process. Results The obtained apparent molecular weight (ca 2 × 105 g/mol) suggested that protein molecules existed as dimers, while the second virial coefficient A2 significantly reduced from −3.98456 × 10−5 to −5.07575 × 10−4 ml mol/g2 when KCl concentrated from 0.15 to 1 mol/L. Light scattering data also suggest that paramyosin dimers are stiff, with a persistence length of 120 nm, almost the length of a molecule and independent of salt concentration. Mean-square displacement (MSD) of tracer particles at 5 temperatures with 4 salt concentrations displayed that this conformation change had dramatic effect. Therefore, G’ and G” were remarkably altered with at least one order of magnitude difference owing to this event occurrence. Conclusions Paramyosin conformation change due to KCl concentrated enhances attractive interactions with apparent molecular mass increase, which resulted in majority paramyosin molecules (> 99%) in dimeric form and promoted aggregates formation. DWS technique revealed that the conformation change dramatic affected this process characterized by the correlation functions, MSD, and G’ and G”. This study brings forward data on understanding the effect of a major salt supplement, KCl, on the chemical physics of a major muscle protein.